(untitled) (Semiárida, 2020)
In this contribution the whole genera and species of the Euphorbiaceae family which grows spontaneously in the Province of La Pampa, Argentine, are listed. This family is represented by 8 genera with 23 species. Keys for the identification of the genera and species are included. A short description, distribution, origin and diffusion in La Pampa of each species are given and 18 species are illustrated.